Characterization of human plasma proteome dynamics using deuterium oxide. Issue 7 (August 2014) - Wang, Ding; Liem, David A.; Lau, Edward; Ng, Dominic C. M.; Bleakley, Brian J.; Cadeiras, Martin; Deng, Mario C.; Lam, Maggie P. Y.; Ping, Peipei; Ge, Ying; Van Eyk, Jennifer
<x xml:space="preserve">Abstract</x> Purpose High‐throughput quantification of human protein turnover via in vivo administration of deuterium oxide (2H2O) is a powerful new approach to examine potential disease mechanisms. Its immediate clinical translation is contingent upon characterizations of the safety and hemodynamic effects of in vivo administration of 2H2O to human subjects. Experimental design We recruited ten healthy human subjects with a broad demographic variety to evaluate the safety, feasibility, efficacy, and reproducibility of 2H2O intake for studying protein dynamics. We designed a protocol where each subject orally consumed weight‐adjusted doses of 70% 2H2O daily for 14 days to enrich body water and proteins with deuterium. Plasma proteome dynamics was measured using a high‐resolution MS method we recently developed. Results This protocol was successfully applied in ten human subjects to characterize the endogenous turnover rates of 542 human plasma proteins, the largest such human dataset to‐date. Throughout the study, we did not detect physiological effects or signs of discomfort from 2H2O consumption. Conclusions and clinical relevance Our investigation supports the utility of a 2H2O intake protocol that is safe, accessible, and effective for clinical investigations of large‐scale human protein turnover dynamics. This workflow shows promising clinical translational value for examining plasma protein dynamics in human diseases.